The new economy - what is really new? - Horst Siebert (Kiel Institute of World Economics (IfW), 2000)
This paper analyzes some of the elements of the new economy. What is really new is first of all the technological innovation. In economic terms what is new is a new product. The new IT product brought about by the new technology means two different things: a new device to handle data and to communicate and a new good "information". This should lead to an increase of productivity, to a larger production potential and to a higher growth rate. The new economy has implications for capital markets and especially for labor. Major issues are regulation and taxation.
Keywords: D2; E1; J2; D0; 330; IT products; productivity effects; impact on growth and on labor; regulation; taxation; new technology; Informationstechnik; Informationsdienstleistung; Produktivität; Wirtschaftswachstum; Faktornachfrage; Informationspolitik; Steuerpolitik; Internationale Arbeitsteilung; Theorie